Disgusted, but amused: positive emotion attenuates disgust elicited by film clips - Mitchell, Benjamin J.; Coifman, Karin G. (Frontiers in Psychology, 2025)
BackgroundDisorders like obsessive-compulsive disorder are associated with heightened disgust. Research suggests that dominant methods for treating such disorders (e.g., exposure therapies) are less effective at targeting disgust. Alternative strategies are needed to enhance treatment effectiveness.MethodsIn two studies, we investigated positive emotion (elicited via humorous content) for attenuating disgust responses to film clips. In Study 1, n = 174 undergraduates were randomized to view either a humorous, sad, or neutral clip prior to a disgusting clip. In study 2, n = 294 undergraduate participants were randomized to either view two clips with discrete emotional content (purely disgusting and purely amusing) or two mixed emotional clips (disgust mixed with amusement, amusement mixed with disgust).ResultsResults of Study 1 showed that the humorous clip buffered against ratings of disgust. In Study 2, humorous content reduced reports of disgust. For both studies, the effect of the manipulation was not moderated by clinical characteristics, like disgust proneness, contamination concerns, or depression.ConclusionFindings suggest that positive emotions can alter the appraisal of disgusting content, attenuating feelings of disgust, with potential clinical implications for treatment.